Collusion in repeated procurement auction: A study of a paving market in Japan - Rieko Ishii (Osaka University, Institute of Social and Economic Research (ISER), 2008)
We examine auction data to determine if bid rigging presents in procurement auctions for paving works in Ibaraki City, Osaka, Japan. We first show that sporadic bidding wars are caused by the participation of potential 'outsiders.' Assuming that the ring is all-inclusive if the auction is not the bidding war, we estimate the scheme by which the ring allocates a win to its members. It is found that the ring tends to select a bidder whose winless period is long and whose winning amount in the past is small relative to other bidders.
Additional information: The Tenth ISER-Moriguchi Prize (2008) Awarded Paper.
Keywords: D44; H57; L44; 330; bid rigging; repeated auction